Kajian Empirik Pilihan Rasional dan Jaringan Nelayan Tani Di Kawasan Danau Tempe - Karim, Mutemainna; Ahmad, Ahfandi; Raisa, Daeva Mubarika; Astaman, Putra; Suryanto (Tarjih : Agribusiness Development Journal, 2023)
This study aims to assess the rationality and social networks formed among fishermen farmers who live and run farms in tidal areas in the Tempe Lake area. The study was conducted in Tempe Lake area, covering Salo Menraleng and Laelo villages, Tempe sub-district, Wajo district from April to May 2016. The assessment method used was the Rapid Rural Appraisal method. Interviews were conducted repeatedly with 2-3 people from the community who work as farmers-fishermen, heads of farmer groups, community leaders and local agricultural extension workers. The interview was considered complete when it had reached a saturation point, i.e. there were no more things to ask. The process of forming rational choices of fishermen farmers who live and run farms in tidal areas in the Tempe Lake area is the existence of actors in this case are fishermen farmers and resources (land) where the relationship between the two is power and interests. The power here means that the landowner fishermen farmers have the right to work on anything in the natural conditions that occur in the Tempe Lake area to fulfill their interests or goals. The goal is to fulfill food needs and a source of family income. This is the reason and background they make decisions or actions in the form of farming methods, cropping patterns, selection of rice varieties and switching from secondary crops to rice. The social network formed among fishermen farmers is a sense of knowing each other, informing each other, reminding and helping in carrying out or overcoming something. Social networks will not materialize without being based on norms and mutual trust. The network of farmer group formation can be used as a means to learn to increase the productivity of their rice farming land.